Radiotherapy-induced Hypothalamic-Pituitary axis dysfunction in adult Brain, head and neck and skull base tumor patients – A systematic review and Meta-Analysis - J.M.J. Paulissen; C.M.L. Zegers; R.M. Houben; D. Hofstede; M. Kars; H.M. van Santen; F.J.P. Hoebers; D.K.M. De Ruysscher; D.B.P. Eekers (Clinical and Translational Radiation Oncology)
Background and purpose: Radiotherapy for brain, head & neck (HN), and skull base (SB) tumors may deliver significant radiation dose to the hypothalamic-pituitary axis (HPA), leading to impaired functioning of this region and hence, to endocrine disorders. The purpose of this systematic review and meta-analysis is to investigate literature on HP dysfunction after radiation for non-pituitary brain, HN, or SB tumors at adult age, aiming to give insight in the prevalence of HP dysfunction related to radiation dose. Materials and methods: Literature search of the PubMed database was performed for HP dysfunction after radiotherapy in adult patients. A risk of bias assessment was performed to rate the quality of the included papers. Besides clinical and treatment variables, reported insufficiencies for adrenocorticotrophic hormone, thyroid stimulating hormone, growth hormone, prolactin and follicle stimulating hormone and luteinizing hormone and for insufficiency of any axis were extracted. The prevalence for hormonal insufficiency per axis and for multiple axes was calculated using a random effects meta-regression with a random effect at the study level. Results: The literature selection process resulted in a total of 22 original papers, suitable for full assessment (n = 1,462 patients). Literature showed a wide variation in HP dysfunction, along with wide dose ranges given to the hypothalamus and pituitary, with varying follow-up times. The calculated prevalence for any pituitary insufficiency was on average 0.61 (95 % CI 0.44–0.75). For growth hormone the mean prevalence was 0.40 (95 % CI 0.22–0.61), for prolactin 0.22 (95 % CI 0.17–0.28), for gonadotropin 0.20 (95 % CI 0.14–0.28), for adrenocorticotropic hormone 0.16 (95 % CI 0.08–0.30) and for thyroid stimulating hormone 0.16 (95 % CI 0.11–0.23). The prevalence for any insufficiency of 1 axis was 0.19 (95 % CI 0.11–0.30), of 2 axes 0.22 (95 % CI 0.12–0.38), of 3 axes 0.05 (95 % CI 0.03–0.09) and of panhypopituitarism 0.17 (95 % CI 0.08–0.32). Patients irradiated for nasopharyngeal carcinoma (NPC) seemed to be at highest risk for developing any endocrine insufficiency with a mean prevalence of 0.68 (95 % CI 0.45–0.85). A significant correlation between any endocrine insufficiency and follow-up time was observed (p = 0.015). A correlation between dose to the pituitary and occurrence of insufficiency on the hormonal axes could not be observed. Conclusion: Endocrine insufficiency is reported in over half of the patients irradiated for brain, HN and SB malignancies. The hypothalamus is likely to be more vulnerable to radiation dose compared to the pituitary gland. More research is needed to establish dose thresholds for the hypothalamus and the pituitary to minimize the risk for pituitary insufficiency. Based on this knowledge, radiotherapy and follow-up of these patient groups should be standardized to establish a normal tissue complication probability (NTCP) model for the HPA.